As vidas do Padre Antônio Vieira: a fabricação do personagem histórico nas escritas da nação (Século XIX) - Macedo, Gil Eduardo Albuquerque (2020)
Greeted as emperor of the Portuguese language, Antônio Vieira was a Jesuit priest who lived between 1608 and 1697. The relevance of the Sermons' author is undoubtedly related to his vast and rich historical experience, but it is with the historiographic investments of the 18th and 19th century that the image of the Jesuit gains visibility in the social imagination. Controversial in life, the readings on the priest were diffuse. With the effervescence of modern history and his relationship with nation projects, the priest became the subject of intense debates, a necessary figure of the Brazilian Historical and Geographic Institute for the formation of the national narrative. A field of disputes was formed around the historical representation of the 17th century priest, from which two interpretations emerged. Symptomatic of the ambiguity generated around the Jesuit, the apologetic image of an individual born in Portugal and who had his homeland duty to Brazil moved along with another model of interpretation: the writing of historical denunciation. In order to understand the appearance of these images and their reverberations, it is essential to understand Vieira's fabrication amid the symbolic investments of 19th century Brazilian historiography. In this sense, we start with the analysis of the historiographic operations of Francisco Adolfo Varnhagen and João Francisco Lisboa, two of the great inventors of the Jesuit priest in 19th century historical culture, with which one can infer a web of adjacent relations, above all, those established with the IHGB and Portuguese historiography